Modal Sosial Sebagai Strategi Kelangsungan Hidup Perempuan Pekerja Seks (Studi Wilayah Transaksi Seksual Teluk Bintuni, Papua Barat dan Pasar Kembang, Kota Yogyakarta) - , LISKA RAHAYU; , Agus Joko Pitoyo., S.Si., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Marginal Community involved in the strategy of self defense for staying survive, one of which choose to become a female sex workers. The increasing number of female sex workers in the city of Yogyakarta, need extra intervention of the Government through social rehabilitation or empowerment programs that not only limited to economic paradigms, but also social paradigm where the dimensions of social capital involved. Space interaction and characteristic of work areas will affect an individual's social capitals in responding to indeterminancy of life.This research was conducted in the area of sexual transactions, Bintuni District and Pasar Kembang, Yogyakarta. Every sexual transaction area was taken samples of 30 sex workers by using a simple random sampling method and indepth interview. The purpose of this research is to analyze 1) the characteristics of sexual transaction area and the female sex workers, considered from the demographic, geography, social and economic variable and 2) the affect their social capital in survival strategies of sex workers in research area. The results showed .The characteristic of sex workers in Bintuni have high mobilityu , dominated by young femaleand spreadly placed among the settlement. Whereas, in Pasar Kembang, the characteristic of sex workers prone to immobility , dominated by old female and concentrate to one specifc area. Social capitals were not only used for the survival of individuals or communities, but also were capable of increasing economic value for theirself. In addition, social capitals also can be a obstruction and driving factor of social interaction, built within a community of sex workers. Effective coordination between sex worker communities, government bodies and non-governmental institutions is expected to increase social capital for sex workers to reduce their vulnerability.